First things first : to live, to love, to learn, to leave a legacy - Covey, Stephen R.; Merrill, A. Roger; Merrill, Rebecca R. (New York : London : Simon & Schuster, Pocket Books, 1994)
A guide to managing your time by learning how to balance your life.
Introduction -- Section one: the clock and the compass -- How many people on their deathbed wish they'd spent more time at the office? -- The urgency addiction -- To live, to love, to learn, to leave a legacy -- Section two: The main thing is to keep the main thing the main thing -- Quadrant II organizing: the process of putting first things first -- The passion of vision -- The balance of roles -- The power of goals -- The perspective of the week -- Integrity in the moment of choice -- Learning from living -- Section three: The synergy of interdependence -- The interdependent reality -- First things first together -- Empowerment from the inside out -- Section four: The power and peace of principle-centered living -- From the management to personal leadership -- The pace of the results.
Includes bibliographical references and index.
Keywords: Conduct of life; Time management